A randomized trial comparing digital video disc with written delivery of falls prevention education for older patients in hospital - Hill, Anne-Marie; McPhail, S.; Hoffmann, T.; Hill, Keith; Oliver, D.; Beer, C.; Brauer, S.; Haines, T. (Wiley-Blackwell Publishing, Inc., 2009)
OBJECTIVES: To compare the effectiveness of a digital video disc (DVD) with that of a written workbook delivering falls prevention education to older hospital patients on self-perceived risk of falls, perception of falls epidemiology, knowledge of prevention strategies, and motivation and confidence to engage in self-protective strategies. To compare the effect of receiving either education approach versus no education on patients' perception of falls epidemiology. DESIGN: Randomized trial (DVD vs workbook) with additional quasi-experimental control group. SETTINGS: Geriatric, medical, and orthopedic wards in Perth and Brisbane, Australia. PARTICIPANTS: One hundred (n=51 DVD, n=49 workbook) hospital inpatients aged 60 and older receiving an intervention (mean age 75.3±10.1) and 122 in the control group (mean age 79.3±8.3). INTERVENTION: Participants randomly assigned to receive identical educational material on falls prevention delivered on a DVD or in a workbook. Control group received usual care. MEASUREMENTS: Custom-designed survey addressing elements of the Health Belief Model of health behavior change. RESULTS: Participants randomized to DVD delivery had a higher self-perceived risk of falling (P=.04) and higher levels of confidence (P=.03) and motivation (P=.04) to engage in self-protective strategies than participants who received the workbook. A higher proportion of participants who received either form of the education provided "desired" responses than of control group participants across all knowledge items (P<.001). CONCLUSION: Delivery of falls prevention education on a DVD compared to a written workbook is more likely to achieve important changes in parameters likely to affect successful uptake of falls prevention messages in the hospital setting. © 2009, The American Geriatrics Society.